IMPACT OF IPSAS ADOPTION ON FINANCIAL MANAGEMENT, ACCOUNTABILITY AND TRANSPARENCY OF SELECTED GOVERNMENT PARASTATALS IN ZARIA - Lawal Mohammed; M. A Odeh; B.F. Umar; U. F. Abdulkarim; S. O. Nurudeen; L Ibrahim (Malete Journal of Accounting and Finance, 2023)
The change in accounting regulations on disclosure is as a result of the weaknesses and low requirements of earlier regulations. IPSAS reporting has more disclosures than former Nigeria cash basis especially for public sector. This study therefore, examines impact of recognition, measurement and disclosure under IPSAS on transparency, accountability and financial management of selected government parastatals in Zaria. Using Census sampling technique, all sixty (60) accounting personnel that were represented in the population were tested. Data was collected with the aid of questionnaire from the selected Parastatal (Ahmadu Bello University, Zaria and the Federal College of Education under the Federal Ministry of Education; the Nigerian Institute for Leather Science and Technology under the Federal Ministry of Science and Technology; the National Institute for Transport Technology; and, the Nigerian College for Aviation Technology under the Federal Ministry of Transport) The study was anchored on institutional and agency theory. Cross sectional research design was adopted, while institutional and agency theory was used to underpin the study. The result shows that disclosure and recognition have significant and positive impact on accountability; financial management and transparency respectively at 1% level of significance. In line with the findings, therefore, we recommend that public sector institutions should adopt IPSAS for better management, accountability and transparency in financial reporting. As IPSAS prescribes a manner in which general purpose financial statements should be prepared